Gesundheitswissen in der Schule Schulhygiene in der deutschsprachigen Schweiz im 19. und 20. Jahrhundert - Hofmann, Michèle (Pädagogik, 2016)
What influence did doctors have on schools? A study on school hygiene from the middle of the 19th century onwards.